ChemInform Abstract: Ca[LiAlN2]: A Quaternary Nitridoaluminate. Issue 47 (4th November 2013) - Pust, Philipp; Pagano, Sandro; Schnick, Wolfgang
Abstract Ca[LiAlN2] is prepared by reaction of LiAlH4, LiN3, and Ca in a lithium flux (weld‐shut Ta crucibles in silica tube, 900 °C, 24 h).